Zmiany podstawowych relacji cen na rynku żywca i mięsa drobiowego w pierwszych miesiącach członkostwa Polski w Unii Europejskiej - Olszańska, Anna (Changes of Basic Relations Between Prices on the Poultry for Slaughter and Poultry Meat Market in the First Month of Polish Membership in EU, 2005)
The aim of this paper is the analysis of changes in relation between purchasing prices, wholesale prices and retail prices on the poultry market. The analysis contains 1995-2004 years, puts special attention to first month of Polish membership in EU. In the most of analyzed years we can observe a strong connection between prices on particular levels of marketing chanel.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 149-154